The Common Marine Policy of the European Union since 2005. (1st January 2012) - Goulielmos, Alexander M.; Lun, Y.H. Venus
In this study we establish and clarify a distinction between 'maritime' and 'marine'. Using this distinction, we propose the establishment of a DG of Marine Clusters in the EU, to integrate marine sectors. Drawing upon the evidence of the 2006 EU Green Paper, the consultation conducted in 2007, and the 2011 white paper, we examine the network of seven EU marine clusters and calculate their contribution to GDP as equal to €242 billion. We also examine the EU's five areas of intervention, including the management of the EU coastal zone. This study emphasises the elusive term 'quality of life', and the importance of the EU in the sustainable development of maritime activities. The challenge of creating a coherent EU vision is also discussed in this study. This vision, however, has become less significant after the EU's budget was fixed at €129.1 billion for 2012 following the deepening crisis that started at the end of 2008. Moreover, the vision of an integrated marine policy lacked quantification – an important characteristic. This has made the implementation of that vision seriously unstable.